Resposta do trigo à aplicação foliar de zinco - Zoz, Tiago [UNESP]; Steiner, Fábio [UNESP]; Fey, Rubens; Castagnara, Deise Dalazen; Seidel, Edleusa Pereira (FapUNIFESP (SciELO), 2012)
Wheat is grown in Brazil, mostly in no-till, a system in which the zinc can become potentially deficient, due to excessive application of acidity corrective and phosphate fertilizers in surface and, or at shallow depths. This study aimed to evaluate the effect of foliar application of zinc in agronomic characteristics and yield of wheat. The experimental design was randomized blocks with five replications. Treatments consisted of four doses of zinc (0, 54, 108 and 216g ha-1 Zn), divided into two foliar applications, the first at tillering (18 days after plant emergence) and the second at the boot stage (65 days after emergence). Foliar application of zinc increased the number of fertile tillers and yield of wheat, however, have little effect on the agronomic characteristics of no-tilled crop with high nutrient content in soil.
Response of wheat to foliar application of zinc
Keywords: Foliar fertilization; Plants nutrition; Tillering; Triticum aestivum